[MEMORANDUM ON THE DRAFT 1991 STATE TAX AND LEGISLATIVE ACTION PLANS] - STUNTZ, SUSAN (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Susan Stuntz to Walter Woodson regarding the 1991 state tax and legislative action plans. Lists specific activity in each separate state. Focuses on the issues of excise taxes, hiring discrimination, privacy, pro-active indoor air quality (IAQ), and vending.